Um olhar de gênero para os processos educativos de empoderamento de mulheres no exercício da presidência de assentamentos rurais de Bananeiras- PB - Silva, Josilene Rodrigues da (2020)
This dissertation takes a look at peasant women leaders of rural settlements and aims to: analyze the educational processes of empowerment of women presidents of rural settlements in Bananeiras, Paraíba. This qualitative study is based on the premise that the empowerment processes of peasant women are educational processes, traversed by gender relations, in which the founding elements of the patriarchal system are still present. The empirical material was produced from six semi-structured interviews with women who held the presidency of rural settlements in the municipality of Bananeiras / PB, two former and four acting presidents. The interviews were analyzed from four axes, as follows: a) Arriving at the presidency; b) Educational processes in the settlement's leadership; c) Meanings attributed to education; d) Gender learning. Despite these women occupying positions of exercise of power, the process of empowerment in this function constitutes a challenge insofar as: women are occupying spaces because men are no longer interested in occupying them; consequently, there is a process of devaluation of the position; women assume the presidency, in general, of a precarious association and without resources, resulting in a presidency that is more representative than effective; a “maternal” perspective of love and care for the settlers stands out. In any case, it is concluded that, even with these challenges, the occupation of the position has a significant weight for these women who become leaders in their settlements. The occupation of the presidency of settlements constitutes for them as educational processes, among them, in relation to gender learning. Such learning changes the perception of these women about themselves, a fact that, consequently, causes transformation in their ways of constituting themselves as women. It can be said, from this, that the empowerment of women is an arduous, gradual and fickle exercise, experienced in different ways.